Ventromedial hypothalamic nucleus neuronal subset regulates blood glucose independently of insulin - Flak, Jonathan N.; Goforth, Paulette B.; Dell’Orco, James; Sabatini, Paul V.; Li, Chien; Bozadjieva, Nadejda; Sorensen, Matthew; Valenta, Alec; Rupp, Alan; Affinati, Alison H.; Cras-Méneur, Corentin; Ansari, Ahsan; et al. (The Journal of Clinical Investigation, 2020)
To identify neurons that specifically increase blood glucose from among the diversely functioning cell types in the ventromedial hypothalamic nucleus (VMN), we studied the cholecystokinin receptor B–expressing (CCKBR-expressing) VMN targets of glucose-elevating parabrachial nucleus neurons. Activation of these VMNCCKBR neurons increased blood glucose. Furthermore, although silencing the broader VMN decreased energy expenditure and promoted weight gain without altering blood glucose levels, silencing VMNCCKBR neurons decreased hIepatic glucose production, insulin-independently decreasing blood glucose without altering energy balance. Silencing VMNCCKBR neurons also impaired the counterregulatory response to insulin-induced hypoglycemia and glucoprivation and replicated hypoglycemia-associated autonomic failure. Hence, VMNCCKBR cells represent a specialized subset of VMN cells that function to elevate glucose. These cells not only mediate the allostatic response to hypoglycemia but also modulate the homeostatic setpoint for blood glucose in an insulin-independent manner, consistent with a role for the brain in the insulin-independent control of glucose homeostasis.